2014
DOI: 10.4103/2229-5151.128010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of performance and utility of mortality prediction models in a single Indian mixed tertiary intensive care unit

Abstract: Objectives:To assess the performance and utility of two mortality prediction models viz. Acute Physiology and Chronic Health Evaluation II (APACHE II) and Simplified Acute Physiology Score II (SAPS II) in a single Indian mixed tertiary intensive care unit (ICU). Secondary objectives were bench-marking and setting a base line for research.Materials and Methods:In this observational cohort, data needed for calculation of both scores were prospectively collected for all consecutive admissions to 28-bedded ICU in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Our findings suggested that abbreviated burn severity index (ABSI) demonstrated high accuracy compared to Ryan, Revised Baux Score, BOBI. This finding supports previous studies which showed good performance of ABSI [ [20] , [21] , [22] ]. The ABSI scoring system remains an accurate and valuable method for determining which is in line with other Swiss Burn Center results [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings suggested that abbreviated burn severity index (ABSI) demonstrated high accuracy compared to Ryan, Revised Baux Score, BOBI. This finding supports previous studies which showed good performance of ABSI [ [20] , [21] , [22] ]. The ABSI scoring system remains an accurate and valuable method for determining which is in line with other Swiss Burn Center results [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding supports previous studies which showed good performance of ABSI [ [20] , [21] , [22] ]. The ABSI scoring system remains an accurate and valuable method for determining which is in line with other Swiss Burn Center results [ 22 ]. Although Ryan, Revised Baux Score, BOBI also showed acceptable accuracy, in clinical practice, ABSI seems to be more easily implemented.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this context, several studies have reported that the Simplified Acute Physiology Score (SAPS) II is superior to APACHE II in predicting mortality [15][16][17][18]. Therefore, the purpose of this study was to propose a new mNUTRIC-S2 (S2 as a reference to SAPS II) scoring system to replace the outdated APACHE II with SAPS II and to compare the ICU mortality prediction ability of the mNUTRIC and mNUTRIC-S2 scores.…”
Section: Introductionmentioning
confidence: 99%